Postsurgical Adjuvant Tumor Therapy by Combining Anti-Angiopoietin-2 and Metronomic Chemotherapy Limits Metastatic Growth - Srivastava, Kshitij; Hu, Junhao; Korn, Claudia; Savant, Soniya; Teichert, Martin; Kapel, Stephanie S.; Jugold, Manfred; Besemfelder, Eva; Thomas, Markus; Pasparakis, Manolis; Augustin, Hellmut G. (Cancer cell, 2014)
Antiangiogenic tumor therapy has failed in the adjuvant setting. Here we show that inhibition of the Tie2 ligand angiopoietin-2 (Ang2) effectively blocks metastatic growth in preclinical mouse models of postsurgical adjuvant therapy. Ang2 antibody treatment combines well with low-dose metronomic chemotherapy (LDMC) in settings in which maximum-dose chemotherapy does not prove effective. Mechanistically, Ang2 blockade could be linked to quenching the inflammatory and angiogenic response of endothelial cells (ECs) in the metastatic niche. Reduced EC adhesion molecule and chemokine expression inhibits the recruitment of tumor-promoting CCR2+Tie2− metastasis-associated macrophages. Moreover, LDMC contributes to therapeutic efficacy by inhibiting the recruitment of protumorigenic bone marrow-derived myeloid cells. Collectively, these data provide a rationale for mechanism-guided adjuvant tumor therapies. [Display omitted] •Seeded metastatic cells create a proinflammatory and immunosuppressive environment•Endothelial cells recruit CCR2+Tie2− metastasis-associated macrophages•Anti-Ang2 Ab plus LDMC is anti-inflammatory and immunomodulatory•Anti-Ang2 Ab plus LDMC is an effective postsurgical adjuvant tumor therapy Srivastava et al. show that combining an antiangiopoietin-2 antibody and low-dose metronomic chemotherapy is a promising postsurgical adjuvant therapy in preclinical cancer models and provide insights into the endothelial contribution to a proinflammatory metastatic niche.